2020
DOI: 10.37570/bgsd-2020-68-04
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous lithostratigraphy of North-East Greenland

Abstract: An updated and revised lithostratigraphic scheme is presented for the Cretaceous of North-East Greenland from Traill Ø in the south to Store Koldewey in the north. The Ryazanian to lower Maastrichtian succession is up to several kilometres thick and comprises four groups, 12 formations and 18 members. The groups record the tectonic evolution of the East Greenland depocentre on the western flank of the evolving proto-Atlantic seaway. The Wollaston Forland Group encompasses the uppermost Jurassic – lowermost Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 7 publications
1
56
0
Order By: Relevance
“…Late Cenomanian -Coniacian The upper Cenomanianlower Turonian interval is poorly represented in north-east Greenland; excepting the succession described here, the interval is known only from scattered outcrops on Traill Ø. The exposed deposits provide a record characterized by deep sea mudstonedominated sedimentation, an absence of largescale turbidite systems, and increasing stratigraphic condensation (Parsons et al, 2017;Bjerager et al, 2020). Whitham et al (1999) reported that theseand other post-Valanginian basinal depositscharacteristically comprise thinly interbedded mudstones and very fine-grained to fine-grained sandstones showing mud-draped ripple cross-lamination; these workers concluded that their emplacement involved bottom current influence.…”
Section: Depositional Processes and Palaeoenvironmental Evolution Of mentioning
confidence: 87%
See 4 more Smart Citations
“…Late Cenomanian -Coniacian The upper Cenomanianlower Turonian interval is poorly represented in north-east Greenland; excepting the succession described here, the interval is known only from scattered outcrops on Traill Ø. The exposed deposits provide a record characterized by deep sea mudstonedominated sedimentation, an absence of largescale turbidite systems, and increasing stratigraphic condensation (Parsons et al, 2017;Bjerager et al, 2020). Whitham et al (1999) reported that theseand other post-Valanginian basinal depositscharacteristically comprise thinly interbedded mudstones and very fine-grained to fine-grained sandstones showing mud-draped ripple cross-lamination; these workers concluded that their emplacement involved bottom current influence.…”
Section: Depositional Processes and Palaeoenvironmental Evolution Of mentioning
confidence: 87%
“…As for other post-Valanginian mudstone-dominated intervals, Whitham et al (1999) interpreted Campanian deposits to have been bottom current influenced. The later Campanian witnessed significant renewed fault activity and the appearance of coarse-grained gravity-flow systems (see Bjerager et al, 2020), but this interval was not encountered in the studied core.…”
Section: Early Campanianmentioning
confidence: 99%
See 3 more Smart Citations